1994
DOI: 10.1002/oms.1210291005
|View full text |Cite
|
Sign up to set email alerts
|

On the gas‐phase reaction of C3O2+. with C3O2

Abstract: The gas-phase, ion molecule reaction between C,O:' and C,O, has been studied by both double-focusing and ion trap mass spectrometry, rationalized by the formation of a dimeric, odd electron cation IC6041+" which decomposes extensively through sequential CO losses giving rise to IC,O,l+. and IC,O,l+' ions. The thermodynamics of this process have been investigated by means of ab initio calculation performed on the above species using different basis sets (STO-3G, 3-21G and 6-31G*).t Present address:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…Ab initio computations have been reported for C 2 O + and for C 2 O +• and C 3 O +• . Pandolfo et al used HF and MP2/6-31G*, hypothesizing an unobserved acyclic dimeric ion C 6 O 4 +• as an intermediate undergoing sequential CO losses leading to C 5 O 3 +• and C 4 O 2 +• . (As discussed in Section , this intermediate and reactions 2 and 3 are not supported by the present work.…”
Section: Introductioncontrasting
confidence: 52%
See 3 more Smart Citations
“…Ab initio computations have been reported for C 2 O + and for C 2 O +• and C 3 O +• . Pandolfo et al used HF and MP2/6-31G*, hypothesizing an unobserved acyclic dimeric ion C 6 O 4 +• as an intermediate undergoing sequential CO losses leading to C 5 O 3 +• and C 4 O 2 +• . (As discussed in Section , this intermediate and reactions 2 and 3 are not supported by the present work.…”
Section: Introductioncontrasting
confidence: 52%
“…• is now found to be linear at its minimum E, a previous study using lower-level theory reported it as quasilinear C 2h . 12 For p even, the calculated electron spin density (Table S7) is nearly equal for all atoms, both C and O, indicating full delocalization of the unpaired electron occupying the highest, partially occupied MOs, π x 1 π y 0 . Spin for CO 2 +• is primarily on the O atoms, but for the other odd-p (3, 5, 7) ions, spin density is localized mainly on C atoms at the even positions.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, O'Hair (Reid et al, 1998, Reid, Simpson, & O'Hair, 1999 and Brodbelt (Felix, Reyzer, & Brodbelt, 1999) have demonstrated the ability of ion traps to do H/D exchange experiments with protonated peptides and nucleoside analogs, respectively. Traldi and co-workers have presented a series of ion trap studies focused on the gas-phase ion chemistry of carbon suboxide (Pandolfo et al, 1994(Pandolfo et al, , 1995Bortolini et al, 1999) as well as the reactions of unusual electrophilic ions formed during chemical ionization (Moneti et al, 1996(Moneti et al, , 1999Bortolini et al, 1998). In addition, Lovejoy (1999) has explored the reactions of protonated H 2 SO 4 /H 2 O clusters with small organic molecules and observed proton transfer as well as H 3 O þ transfer and hydride abstraction.…”
Section: F Miscellaneous Reactionsmentioning
confidence: 97%